THE EFFECT OF CLIMATE CHANGE ON FINANCIAL MARKET STABILITY IN IRAN - Azadeh Zekri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The fluctuation of financial markets is one of the main factors that can affect the economic conditions of society and leads to increase or decrease inflation. One of the factors affecting the stability of the financial market is climate fluctuations, which can lead to fluctuations in the financial market. Given that the stability of the financial market is important in any economy, the present study is aimed at investigating the impact of climate change on the stability of the financial market. For this purpose, the statistical population of this study is the Iranian economy during the years 1395 to 1397. Financial data extracted from Tehran Stock Exchange, and Central Bank, also for the data related to climate change we have used the site of the Meteorological Organization, and the results were analyzed by using Eviews9 software. The results of data analysis showed that climate change has a significant effect on the stability of the financial market, which includes changes in temperature, cloud cover per day, humidity, wind, snow, and rain. Considering the importance of financial market stability, it can be concluded that in the case of climate fluctuations, financial market stability will also fluctuate. Abbreviations: AIC: Akaike information criterion, CO2: Carbon Dioxide, FPE: Final Prediction Error, GDP: Gross Domestic Product, HQ: Hannan Quinn, VAR: Vector Autoregressive, SC: Schwarz-Bayesian criterion.